2011
DOI: 10.1007/s11274-011-0775-6
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and bioinformatics analysis of a novel acidophilic β-mannanase gene, Auman5A, from Aspergillus usamii YL-01-78

Abstract: The full-length cDNA sequence, which encodes a novel acidophilic b-mannanase (abbreviated as AuMan5A) of Aspergillus usamii YL-01-78, was amplified by 3 0 and 5 0 rapid amplification of cDNA ends (RACE) using the total RNA as template. The cDNA sequence is 1,427 bp in length, including 5 0 and 3 0 non-coding regions and an open reading frame (ORF). The ORF encodes a 21-aa signal peptide, a 17-aa propeptide, and a 345-aa mature peptide (AuMan5A) with the calculated M.W. of 37,614 Da and pI of 4.09 and two putat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…Propeptides also exist in other β-mannanases or microbial enzymes. , A theoretical molecular weight of the AnMan5A is 37 539 Da that is in good agreement with the determined molecular weight (37.5 kDa) of the deglycosylated A. usamii AuMan5A, and a calculated pI is 4.15 that is similar to that (pI 4.2) of the purified A. usamii AuMan5A determined by isoelectric focusing (IEF)–PAGE .…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Propeptides also exist in other β-mannanases or microbial enzymes. , A theoretical molecular weight of the AnMan5A is 37 539 Da that is in good agreement with the determined molecular weight (37.5 kDa) of the deglycosylated A. usamii AuMan5A, and a calculated pI is 4.15 that is similar to that (pI 4.2) of the purified A. usamii AuMan5A determined by isoelectric focusing (IEF)–PAGE .…”
Section: Resultssupporting
confidence: 69%
“…To make β-mannanases be applied more efficiently and economically, more interests are being focused on improving their structures and catalytic properties with chemical or physical approaches and, recently, by means of genetic engineering. Many β-mannanase genes from filamentous fungi, such as Aspergillus niger CBS 513.88, Aspergillus usamii YL-01-78, Aspergillus sulphureus MAFIC001, Aspergillus aculeatus MRC11624, Biopora sp. MEY-1, and Trichoderma reesei RutC30, have been cloned, characterized, and modified, and some recombinant β-mannanases have been expressed in heterologous cells with high activities and superior properties. , …”
Section: Introductionmentioning
confidence: 99%
“…Generally, fungal β-mannanases are mainly effective at acidic to neutral pH [10]. Compared with the close homologues from A. sulphureus (ABC59553.1) [14], A. usamii YL-01-78 (ADZ99027.1) [26], and E. nidulans (ABF50863.1) [27] that have optimal activities at acid pH but are not stable in alkaline conditions, MAN5 has an acidic pH optimum (pH 6.0) and remains stable in acidic to alkaline conditions (pH 4.0-11.0). It has been reported that the pH property of an enzyme is determined by its amino acid composition, secondary structure, hydrogen bonds and ion pairs, protein surface structure, and active site [12].…”
Section: Discussionmentioning
confidence: 99%
“…The overall deduced amino acid sequence of MAN5 exhibited the highest identity of 58% with an endo-1,4-β-mannanase from Aspergillus aculeatus [25] and 47-48% identities with β-mannanases from A. sulphureus (ABC59553.1) [14], Aspergillus usamii YL-01-78 (ADZ99027.1) [26], and Emericella nidulans (ABF50863.1) [27]. Sequence alignment of catalytic domains of MAN5 and other fungal mannanases (Fig.…”
Section: Cloning and Sequence Analysis Of Man5mentioning
confidence: 99%
“…In our previous work, an AuMan5A-encoding gene ( Auman5A ) was cloned and analyzed. The multiple sequence alignment among family 5 β-mannanases displayed that no CBM was found in the AuMan5A [12]. To perfect the AuMan5A’s properties, our present work designed an AuMan5A-CBM by fusing a CBM of the TrCBH I into the AuMan5A.…”
Section: Introductionmentioning
confidence: 99%